2013
DOI: 10.1007/s00421-013-2714-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses to a 48-h ultra-marathon run in middle-aged male amateur runners

Abstract: PurposeTo evaluate ongoing metabolic changes during a 48-h competitive run and a 48-h recovery period, with focus on potential health risks exemplified by heart and skeletal muscle damage biomarkers and oxidative stress-related indices.MethodsBlood samples were taken before the race, after 12, 24, and 48 h of running, and after 24 and 48 h of recovery from male amateur runners (N = 7, age 35–59 years, VO2max mean ± SD 57.0 ± 4.0 ml kg−1 min−1, total distance covered 183–320 km). The samples were analyzed for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
111
1
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(144 citation statements)
references
References 73 publications
(92 reference statements)
23
111
1
9
Order By: Relevance
“…Running speed decreased along with each 25 km stretch in all the subjects ( Table 1). The mean running speed value during the whole 100-km distance was 8.33 km/h, which is in line with the results revealed by Kłapcińska et al [29]. Parameters of the blood counted both during the run and recovery did not exceed the reference data.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Running speed decreased along with each 25 km stretch in all the subjects ( Table 1). The mean running speed value during the whole 100-km distance was 8.33 km/h, which is in line with the results revealed by Kłapcińska et al [29]. Parameters of the blood counted both during the run and recovery did not exceed the reference data.…”
Section: Discussionsupporting
confidence: 91%
“…No statistically significant changes in HB, HCT, RBC, MCH, MCV, MCVC and blood platelets were found during either the run or the recovery. Kłapcińska et al [29] and Waśkiewicz et al [28] have reported similar findings. However, Wu et al [27] have observed a decrease in RBC related to haemolysis [32] and damage caused by reactive oxygen species (ROS) [33] that occurred between the second and ninth day of recovery after termination of a half-marathon.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Leukocytes and neutrophils increased by more than two times in a small group of subjects at the end of an ultra-marathon and returned to baseline values 24 h after. 16 Also milder physical efforts may significantly increase WBC count, as shown in healthy volunteers after 5 min of self-paced peak cycle ergometry. In this case, leukocyte counts returned to baseline values in 3 h. 17 These findings, obtained in well-controlled experimental conditions, suggest that both physical and emotional stress increase WBC count and thus could support our hypothesis.…”
Section: Transient Leukocytosis In Emergency Roommentioning
confidence: 93%
“…For example, a 48-h ultra-marathon caused hypocapnic alkalosis with slight hyperkalemia and hypocalcemia, but no hyponatremia. Blood biochemistry showed severe muscle but not liver damage, and an acute inflammatory response [83]. Most of the changes were dissolved after 48 hours of recovery [83].…”
Section: Pathophysiological Effects Of Ultra-marathon Runningmentioning
confidence: 99%